Church, state, morality and law - Hannon, Patrick (Dublin, Ireland Gill and Macmillan, 1992)
Includes bibliographical references.
Keywords: Ethics -- Religious aspects -- Christianity; Politics -- religious aspects -- Christianity; Law -- religious aspects -- Christianity